CHARACTERIZATION OF SUICIDE ATTEMPTS AMONG THE ELDERLY - Maycon Rogério Seleghim; Ana Carolina Manna Bellasalma; Thais Aidar de Freitas Mathias; Magda Lúcia Félix de Oliveira (Universidade Federal do Paraná, 2012)
This retrospective study aimed to characterize the suicide attempts among the elderly registered between January 2004 and December 2010 in a Toxicological Care and Information Center in Paraná. The data was collected from the records of toxicological events from 66 suicide attempts; the socio-demographic and clinical variables were processed using the software Statistics 7,0®, and a Chi-squared test was applied at the 5% significance level. The suicide attempts among the elderly represented 2,47% of the total of attempts registered, and happened among individuals aged from 60 to 69, with up to eight years of education, retired, from the city of Maringá and the metropolitan region. The attempts were made with pesticides or herbicides used in agriculture or with medicines used in psychiatric treatment. It is concluded that the characterization of suicide attempts in this population permits the planning of actions for preventing this event.